Seëls as getuies van buitelandse invloede in Palestina gedurende die Persiese periode - Vermeulen, Floris (Journal for semitics, 2007)
Seals developed in conjunction with writing and for more than seven thousand years it played a major role in establishing modern civilisation. From textual sources not much is known about the foreign influences prevalent in Palestine during the Persian Period. The Persians, in contrast to their predecessors, the Assyrians and the Babylonians, were much more liberal in their treatment of conquered nations. They allowed interaction between such nations amongst themselves and also with other nations. The personal nature of seals leads to conclusions about their origin and the influences contributing to their creation. From the study of seals it is possible to establish that there were inter alia Babylonian, Persian, Greek and Egyptian influences prevalent in Palestine during the relevant period.